2003
DOI: 10.1016/s1055-7903(02)00298-1
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequencing of wsp encoding gene fragments reveals a diversity of co-infecting Wolbachia strains in Acromyrmex leafcutter ants

Abstract: By sequencing part of the wsp gene of a series of clones, we detected an unusually high diversity of nine Wolbachia strains in queens of three species of leafcutter ants. Up to four strains co-occurred in a single ant. Most strains occurred in two clusters (InvA and InvB), but the social parasite Acromyrmex insinuator hosted two additional infections. The multiple Wolbachia strains may influence the expression of reproductive conflicts in leafcutter ants, but the expected turnover of infections may make the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
62
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 45 publications
8
62
0
1
Order By: Relevance
“…Wolbachia has been found in several sexually reproducing ant species ( Wenseleers et al 1998) including fungus-growing ants (Van Borm et al 2003), but is absent in seven partially asexual ant species (Wenseleers & Billen 2000;Fournier et al 2005;Pearcy et al 2005). We document here that endosymbiotic microbes also appear to be absent in the asexual M. smithii.…”
Section: Discussionmentioning
confidence: 57%
“…Wolbachia has been found in several sexually reproducing ant species ( Wenseleers et al 1998) including fungus-growing ants (Van Borm et al 2003), but is absent in seven partially asexual ant species (Wenseleers & Billen 2000;Fournier et al 2005;Pearcy et al 2005). We document here that endosymbiotic microbes also appear to be absent in the asexual M. smithii.…”
Section: Discussionmentioning
confidence: 57%
“…Horizontal transmission could explain why closely related Wolbachia occur in the distantly related ant genera Acromyrmex, Solenopsis, and Linepithema. The vector of horizontal transmission could have been parasites or parasitoids specialised on ants (van Borm et al, 2003). Finally, it should be noted that sequence similarity might also stem from homologous recombination between Wolbachia lineages.…”
Section: Discussionmentioning
confidence: 99%
“…None of the other OTUs was restricted to or specific for any of the three Acromyrmex ant species (see Table S4A in the supplemental material). We further characterized the RhiAcro1, EntAcro1, and EntAcro2 OTUs using Sanger sequencing and obtained 982-bp, 1,282-bp, and 1,340-bp sequences, respectively, while the WolAcro1 OTU has been characterized previously (48,49). Maximum-likelihood phylogenetic trees showed that RhiAcro1 is closely related to Rhizobiales strains identified in Trachymyrmex urichii of the attine lineage (see Fig.…”
Section: S-454 and 16s-miseq Sequencingmentioning
confidence: 99%